2012
DOI: 10.1158/1078-0432.ccr-12-0035
|View full text |Cite
|
Sign up to set email alerts
|

miRNA Biomarkers in Cyst Fluid Augment the Diagnosis and Management of Pancreatic Cysts

Abstract: Purpose The diagnosis of pancreatic cystic lesions has increased dramatically. Most are benign, whereas some, such as intraductal papillary mucinous neoplasms (IPMN), represent precursors of pancreatic adenocarcinoma. Therapeutic stratification of IPMNs is challenging without precise information on dysplasia grade and presence of invasion. We assessed the diagnostic benefit of using miRNAs as biomarkers in pancreatic cyst fluid, focusing on IPMNs because of their frequency and malignant potential. Experiment… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
125
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(130 citation statements)
references
References 44 publications
3
125
2
Order By: Relevance
“…Several studies have found that mRNA markers have a high sensitivity and specificity (>80%) for identifying cyst type and IPMNs with high-grade dysplasia or invasive pancreatic adenocarcinoma [17,18]. However, all the studies are single-center, retrospective studies with very few markers evaluated in more than one report.…”
Section: Intraductal Papillary Mucinous Neoplasms and Mucinous Cysticmentioning
confidence: 99%
“…Several studies have found that mRNA markers have a high sensitivity and specificity (>80%) for identifying cyst type and IPMNs with high-grade dysplasia or invasive pancreatic adenocarcinoma [17,18]. However, all the studies are single-center, retrospective studies with very few markers evaluated in more than one report.…”
Section: Intraductal Papillary Mucinous Neoplasms and Mucinous Cysticmentioning
confidence: 99%
“…Chemical analysis of cyst fluid, in particular CEA level, was suggested by some groups to predict malignancy 36,37 but has not been reproducible. 19,38 Molecular assessment of cyst fluid (eg, DNA analysis for oncogenic KRAS or GNAS mutations and/or amplifications), 38,39 Kim & Fernandez-del Castillo microRNA (miRNA) profiling, 40 cytokine measurement (eg, of interleukin [IL]-1ß 41 and prostaglandin E 2 [PGE 2 ]), 42 and mucin proteomic profiling 43 may each improve prediction of malignancy but require further investigation. Overall, EUS/FNA is promising but prone to interobserver variability and operator dependency, should be performed in centers with expertise in these techniques, and requires further validation prior to widespread use.…”
Section: Current Controversies and Future Directionsmentioning
confidence: 99%
“…Cyst fluid may be used to detect high-risk IPMNs employing the Das-1 monoclonal antibody raised against a reactive premalignant colonic epithelial phenotype [35] . A 9 miRNA panel may also be able to distinguish high-grade IPMNs, PNETs and pseudopapillary neoplasms from low-grade IPMNs and SCNs [36] . Most recently cyst fluid VEGF-A levels were found to be significantly upregulated in test series of SCNs compared with other pancreatic cysts and with a cutoff of 8,500 pg/ml, VEGF-A had a 100% sensitivity and 97% specificity as an SCN biomarker [37] .…”
Section: Discussionmentioning
confidence: 99%